2021
DOI: 10.3389/fendo.2021.632284
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Targets and Nutritionally Relevant Intervention Strategies to Break Obesity–Breast Cancer Links

Abstract: The worldwide prevalence of overweight and obesity has tripled since 1975. In the United States, the percentage of adults who are obese exceeds 42.5%. Individuals with obesity often display multiple metabolic perturbations, such as insulin resistance and persistent inflammation, which can suppress the immune system. These alterations in homeostatic mechanisms underlie the clinical parameters of metabolic syndrome, an established risk factor for many cancers, including breast cancer. Within the growth-promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 180 publications
(204 reference statements)
0
9
0
Order By: Relevance
“…Moreover, leptin is important in both initiating and fostering disease progression through its links to an obesogenic environment which allow deleterious crosstalk between three other mechanisms in addition to adipose-derived chronic inflammation, including the interplay with the leptin receptor, dysfunction in endocrine regulation of the sex hormones, as well as the altered signaling networks triggered by elevated levels of circulating insulin and IGF-1 receptors ( 122 ). High leptin production caused by the dysfunction of or excess adipose tissue is often seen in obesity and cancer, notably in breast cancer ( 123 ). Based on the inclusion criteria for this review, two papers identified leptin measurement as a useful breast cancer inflammatory biomarker, particularly in relation to exercise ( 88 ) or loss of body fat ( 64 ), and the potential for these two factors to decrease of leptin levels, resulting in improved the disease outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, leptin is important in both initiating and fostering disease progression through its links to an obesogenic environment which allow deleterious crosstalk between three other mechanisms in addition to adipose-derived chronic inflammation, including the interplay with the leptin receptor, dysfunction in endocrine regulation of the sex hormones, as well as the altered signaling networks triggered by elevated levels of circulating insulin and IGF-1 receptors ( 122 ). High leptin production caused by the dysfunction of or excess adipose tissue is often seen in obesity and cancer, notably in breast cancer ( 123 ). Based on the inclusion criteria for this review, two papers identified leptin measurement as a useful breast cancer inflammatory biomarker, particularly in relation to exercise ( 88 ) or loss of body fat ( 64 ), and the potential for these two factors to decrease of leptin levels, resulting in improved the disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the study that analyzed the effect of exercise on localized breast cancer, although leptin was decreased in both the intervention group and control group (i.e., with no significant difference in biomarker levels between groups), authors pointed out that high leptin level and low adiponectin level were also associated with increased risk of breast cancer recurrence and mortality ( 88 ). Thus, besides leptin alone, the adiponectin/leptin ratio is also associated with indication of breast cancer progression ( 123 ). A multiethnic case-control study further demonstrated that a reduced adiponectin/leptin ratio was associated with increased risk of postmenopausal breast cancer, which was also shown in preclinical models ( 124 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, we observed some upregulation in pathways related to cancer. This is relevant as murine obesity cancer progression and metastasis (51); therefore, obesity may be targeting pathways that are of interest to lung cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Hard data synthesize evidence on the biological mechanisms underlying obesity-breast cancer links [12]. Similarly, obesity and dysregulated metabolism in night-shift workers [13] could increase breast cancer risk [14].…”
Section: Discussionmentioning
confidence: 99%